Electroluminescent segmented liquid crystalline trimers - Aldred, M.P.; Hudson, R.; Kitney, S.P.; Vlachos, P.; Liedtke, A.; Woon, K.L.; O'Neill, M.; Kelly, S.M. (Taylor & Francis, 2008)
The synthesis and liquid crystal behaviour of light‐emitting trimeric liquid crystals consisting of three mesomorphic moieties connected by aliphatic spacers are reported. The combination of an aromatic light‐emitting central core and two cholestanyl (dihydrocholesteryl) groups induces a helical liquid crystalline phase with circularly polarised photoluminescence and electroluminescence. These segmented trimers are designed to possess a high glass transition temperature below which the structure of liquid crystalline phases can be fixed. The effects of odd and even spacers, spacer length and the presence of large lateral substituents on the liquid crystal behaviour and the glass transition temperature of these trimers were studied. Electroluminescence from a segmented liquid crystalline trimer is reported for the first time.